Role of Steroid in Adult Patients of Septic Shock - A Critical Analysis - Hasan, Rajib; Kabir, Humayun; Roy, Taposh Chandra; Chowdhury, Javed Sharoar; Yeasmin, Farzana (KYAMC Journal, 2017)
" Sepsis and septic shock is the condition which has been with intensive care units from long before. In fact, it is one of the highly ranked diseases causing mortality in ICU patients. There are currently many evidence based practices in the management of septic shock and use of steroid is one of them. The aim of this article is to critically evaluate the evidences regarding the role of steroids in adult patients of septic shock. This article has also evaluated all the current evidences regarding details of the role of steroids including their formulation, dosage, duration and route of administration in patients of septic shock. KYAMC Journal Vol. 4, No.-2, Jan 2014, Page 409-414